ANALISIS DISKRIMINAN BAURAN PEMASARAN TERHADAP PERSEPSI KONSUMEN UNTUK MEMUTUSKAN PEMBELIAN SEPEDA MOTOR MATIC MEREK HONDA DAN YAMAHA DI STIE DEWANTARA - Benny Osta Nababan; Billy Permana (Economicus : Jurnal Ekonomi dan Manajemen, 2020)
This research was conducted to determine differences in consumer perceptions of Honda and Yamaha brand motorcycles. Data were collected by survey technique to 100 students of STIE Dewantara who used automatic motorcycles from Honda and Yamaha in 2013 and above. The results obtained from this study: (1) the score on the test of the greater difference in average Honda motorcycles compared to Yamaha; (2) there are 4 differences in variables between groups, product variables, location and promotion making the reason for consumers to decide to buy a Honda motorcycle while for consumer price variables prefer to buy a Yamaha motorcycle; (3) There are differences in behavior between Honda and Yamaha motorcycle users because they have a sig <0.1 value in the Entered / Removed Variables table; (4) Dependent variable (Y) can be explained by all independent variables (product, price, location and promotion) of 75.34%, which means that all independent variables have a positive effect on the dependent variable (Y) of purchasing decisions; (5) Honda motorcycles have a positive sign (+) with independent variables (product, location and promotion) while Yamaha motorbikes have a negative sign (-) with independent variables (price); (6) The discriminant model is suitable to be used and is able to classify it properly for discriminant analysis in this study because it obtained a high accuracy rate of 96%.